2017
DOI: 10.1016/j.surg.2016.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of methane preserves the epithelial barrier during ischemia and reperfusion in the rat small intestine

Abstract: Normoxic methane decreases the signs of oxidative and nitrosative stress, improves tissue microcirculation, and thus appears to modulate the ischemia-reperfusion-induced epithelial permeability changes. These findings suggest that the administration of exogenous methane may be a useful strategy for maintaining the integrity of the mucosa sustaining an oxido-reductive attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In our study, myeloperoxidase (MPO) whose activity is assessed during evaluation of intestinal ischemic injury, was shown to be an enzyme released due to neutrophil activation and is present during the production of free oxygen radicals [15,16]. Various studies have demonstrated that increase in MPO activity as a sign of neutrophil infiltration during mesenteric I/R injury causes endothelia dysfunction and inflammation [17,18]. In our study, MPO values increased significantly with I/R, consistent with literature results.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, myeloperoxidase (MPO) whose activity is assessed during evaluation of intestinal ischemic injury, was shown to be an enzyme released due to neutrophil activation and is present during the production of free oxygen radicals [15,16]. Various studies have demonstrated that increase in MPO activity as a sign of neutrophil infiltration during mesenteric I/R injury causes endothelia dysfunction and inflammation [17,18]. In our study, MPO values increased significantly with I/R, consistent with literature results.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, such analyses indicated that the circulating microbiome of NACs were enriched with respect to methanogenesis, denitrification, and several other functions. A growing body of literature indicates an important role of gases as “signaling” molecules, and both methane and hydrogen sulfide have been implicated as regulators of intestinal epithelial integrity and gut‐derived inflammatory signals . A likely possibility is that circulating bacteria, by producing even minute quantities of such gases, and/or pathogen‐associated molecular patterns may modulate signaling within the innate and adaptive immune system, modify oxidative stress, and affect the microcirculation and even cellular function in individual organs.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature indicates an important role of gases as "signaling" molecules, and both methane and hydrogen sulfide have been implicated as regulators of intestinal epithelial integrity and gut-derived inflammatory signals. (35,36) A likely possibility is that circulating bacteria, by producing even minute quantities of such gases, and/or pathogen-associated molecular patterns may modulate signaling within the innate and adaptive immune system, modify oxidative stress, and affect the microcirculation and even cellular function in individual organs. This possibility is further supported by the well-established roles of nitric oxide and carbon monoxide as modulators of endothelial dysfunction, microcirculation, organ function, and inflammation, particularly in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro results substantiated the in vivo findings, and established that CH 4 exposure specifically decreases the ROS production of activated PMN leukocytes (Boros et al, 2012). In another study normoxic ventilation with 2.5% CH 4 maintained the superficial mucosal structure, the reperfusion-induced epithelial hyperpermeability was significantly alleviated and the microcirculatory flow reduction was prevented (Mészáros et al, 2017a).…”
Section: Anti-inflammatory and Anti-apoptotic Effects During Ischemiamentioning
confidence: 99%